Effects of Shoe-Attached Location-Tracking Devices on People with Mild Cognitive Impairment and Their Caregivers: A Pilot Study. - Hwang, Yeji; Hwang, Mina; Han, Yunji; Kim, Jayeong (Clinical Gerontologist)
Objectives: Wandering is common in people with memory impairment and increases caregivers' stress and burden. Given that people wear shoes when going out, this study aimed to apply a shoe-attached location-tracking device to individuals with mild cognitive impairment (MCI) and evaluate their effectiveness. Methods: Participants were 23 dyads, including a person with MCI and a family caregiver. The individuals with MCI wore a location-tracking device on their shoes for eight weeks. The study was a multi-method study and included quantitative and qualitative components. A one-group pretest-posttest design was employed to evaluate the effectiveness of the intervention quantitatively, while posttest interviews enabled qualitative examination of participants' experiences. Results: After the location-tracking devices were applied, caregivers were more likely to allow their loved ones to go out alone (p =.01). Qualitative analyses revealed four themes: (1) satisfaction with the location-tracking device, (2) specific benefits of the shoe-attached location-tracking device, (3) fear of judgment from others, and (4) suggestions for future enhancements. Conclusions: The shoe-attached location-tracking device was helpful to both individuals with MCI and their family caregivers, indicating potential for wider adoption. Clinical Implications: Making the device widely available can improve well-being of people with MCI and their caregivers.